INTEGRASI PASAR KOMODITAS KELAPA DAN PRODUK TURUNAN INDONESIA DENGAN PASAR DUNIA - Syahrul Ganda Sukmaya; Reny Hidayati (Mimbar Agribisnis: Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2020)
Coconut products are mostly traditional export Indonesia. Coconut products seed is copra exports and coconut oil. The determination of product price coconut export determined by reference the world market often known only by some side. Asymmetrical market information received by producers can harm producers. Fluent market information can help improve the welfare of producers and increase the speed reaction producers on changes in the market. Through research, market integration is expected to determine the level of integration of Indonesian market reference world markets. Benefit from the study that can be done the next step and anticipation of to increase the market information for producers. Eventually with the market information obtained can improve producers when reaction that is a massive market, and the welfare of oil producer. To assess integration this market used method of var/vecm. The result showed that the Indonesian coconut by integrated with coconut the world market. On the Indonesian market, market integration that happened between copra market indonesia and palm oil market indonesia is market integration in line because of only coconut oil prices significant on the amount of copra Indonesia, and vice versa.